Interference of electron wave packets in photoionization of by attosecond ultraviolet laser pulses - Yu, Hua-Ming; Yuan, Kai-Jun (Journal of modern optics, 2017)
We study molecular photoionization of aligned by a sequence of two attosecond ultraviolet laser pulses at frequencies and from numerical solutions of time-dependent Schördinger equations. Results exhibit signature of interference effects of coherent electron wave packets, which is shown to be sensitive to the time delay between the two pulses. It is found that for the photoionization with identical frequencies , same interference distributions are produced in the positive and negative momentum regions whereas for the case of , photoelectron momentum distributions are asymmetric. Influence of the pulse carrier envelope phase is also presented. The attosecond perturbation theory is used to describe these interference phenomena.